On Verbal Tools To Open Our Past And Future Wider - Vitaliy Radchuk (Cхід)
The article substantiates a need to widen the arsenal of lingual and logical tools of historical and prognostic kinds of thinking offering to remove some restrictions as biased and braking. It is argued that human history is only enriched with human modal logic, in particular with the Conditional Mood that has been repressed by the objectivists. Also discussed are principles of linguistic futurology that is tabooed by narrow-minded political interest. A study of trends and laws of development in dynamic lingual sphere allows the author to foreсast some results of the interaction of Ukrainian, Russian and English in Ukraine. As it always has been under similar circumstances in the past, one observes changes today in each tongue in the media of mixing along with a contest of variants of the future lingual hybrid.